Gliadin Degradation Ability of Artisanal Lactic Acid Bacteria, The Potential Probiotics from Dairy Products - Komen, Gokcen; Baysal, Ayse Handan; Harsa, Hayriye Sebnem (Journal of Nutritional Therapeutics, 2013)
Selected Lactobacillus spp. with high protease and acid producing capacity was explored for effective gliadin degradation in wheat sourdough environment. The total titratable acidity (TTA), pH and lactic acid bacteria (LAB) counts were evaluated. At the end of fermentation, the acidity and pH of the sourdough samples reached to 13.49-17.34 and 3.84-3.52 range, respectively. LAB population was enumerated as 107-109 colony forming unit (CFU)/g dough. Gliadin profiles were examined qualitatively using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE), two-dimensional electrophoresis (2-DE) and reverse phase-high performance liquid chromatography (RP-HPLC) techniques. Especially RP-HPLC could be considered as a sensitive technique and is useful to determine the biochemical changes in gliadin fragmentation throughout sourdough fermentation process. LAB inoculated sourdoughs and chemically acidified sourdoughs generally represent similar gliadin degradation patterns. Although the total removal of gliadin toxicity could not be achieved in all dough formulations, it may be beneficial to use LAB to improve the dough and bread quality through the exploration of its bioconversion by-products.